2019
DOI: 10.3389/fgene.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model of Human Behavior Provides Evidence of Natural Selection Against Underexpression of Aggressiveness-Related Genes in Humans

Abstract: Aggressiveness is a hereditary behavioral pattern that forms a social hierarchy and affects the individual social rank and accordingly quality and duration of life. Thus, genome-wide studies of human aggressiveness are important. Nonetheless, the aggressiveness-related genome-wide studies have been conducted on animals rather than humans. Recently, in our genome-wide study, we uncovered natural selection against underexpression of human aggressiveness-related genes and proved it using F1 hybrid mice. Simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…We found that selection on social behavior has altered the anatomy of distributed gray matter networks which included, among other regions, prefrontal cortex, hippocampus, amygdala, caudate, nucleus accumbens, cerebellum, and hypothalamus. This agrees generally with past findings in these foxes 1923 and on the neural correlates of wolf-to-dog domestication 810,1921,3033 . Although some of our prefrontal results are located on the dorsolateral surface of the brain (i.e., the prorean gyrus), this region is likely not homologous to the granular dorsolateral prefrontal cortex of humans and macaque monkeys, as that region is thought to be unique to primates 34,35 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that selection on social behavior has altered the anatomy of distributed gray matter networks which included, among other regions, prefrontal cortex, hippocampus, amygdala, caudate, nucleus accumbens, cerebellum, and hypothalamus. This agrees generally with past findings in these foxes 1923 and on the neural correlates of wolf-to-dog domestication 810,1921,3033 . Although some of our prefrontal results are located on the dorsolateral surface of the brain (i.e., the prorean gyrus), this region is likely not homologous to the granular dorsolateral prefrontal cortex of humans and macaque monkeys, as that region is thought to be unique to primates 34,35 .…”
Section: Discussionsupporting
confidence: 93%
“…These latter measurements revealed links with individual variation in behavior, including in brain regions that did not show volumetric differences, notably, the hypothalamus. Additionally, Network 3 consisted primarily of the hypothalamus and prefrontal cortex, two regions strongly implicated in both fox and dog domestication [8][9][10][19][20][21][30][31][32][33] . In this network, factor loadings did not differentiate the tame from aggressive strains; rather, the selectively-bred strains together were differentiated from the conventional strain ( Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral "Glove" Test [20] respectively. Filled circles depict the statistically significant DEGs in the hypothalamus of tame vs. aggressive rats according to the independent qPCR-based identification published elsewhere [34]. These qPCR [34] and RNA-Seq [this work] data are given in Table S1, where their Pearson's linear correlation is statistically significant, r = 0.71 at p < 0.05 (hereinafter, see Supplementary Materials).…”
Section: Methodsmentioning
confidence: 99%
“…We developed our Web service SNP_TATA_Comparator 1 (Ponomarenko et al, 2015), whose input consists of two promoter DNA sequences representing ancestral and minor alleles of the SNP being examined; the software generates TBP-binding affinity estimates for these promoter alleles (± standard error) and significance α of their difference with Fisher's Z-test (Waardenberg et al, 2015). We applied it from SNP to SNP to predict their contribution to diseases [e.g., chronopathologies (Ponomarenko et al, 2016)] and selectively verified the obtained results using F1-hybrid mice , real-time polymerase chain reaction (Oshchepkov et al, 2019), RNA-Seq data (Vasiliev et al, 2021), gel retardation assay, stopped-flow spectrometry, biosensors, or bioluminescence, as reviewed (Ponomarenko et al, 2017). SNP_TATA_Comparator (Ponomarenko et al, 2015) is already used in independent clinical studies [e.g., in a pulmonary tuberculosis case-control study (Varzari et al, 2018)].…”
Section: Introductionmentioning
confidence: 99%